Analysis of Disease Free Survival and Overall Survival of HER2 Positive Subtype Breast Cancer Patients at Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital - Kamajaya, Gde Ary Putra; Wetan, Ni Gusti Ayu Agung Manik Yuniawaty; Setiawan, I Gede Budhi (JBN (Jurnal Bedah Nasional), 2025)
Aim: This study aim to assess the characteristics of the patients, as well as the 3-year and 5-year overall survival and disease free survival of HER2+ breast cancer patients treated at Prof. Dr. I.G.N.G. Ngoerah Hospital Denpasar Methods: This retrospective cohort study assessed survival rates and prognostic factors among HER2+ breast cancer patients treated at Prof. Dr. I.G.N.G. Ngoerah Hospital Denpasar from January 2017 to December 2022. The study used medical records to examine variables such as age, tumor characteristics, metastasis patterns, histology, treatments, and survival outcomes over 3- and 5-year periods. Results: The 3-year survival rate was 77.7% and the 5-year survival rate was 74.3%, with median survival times of 31 months (95%CI 30.7-32.86) and 49 months (95%CI 47.85-52.089), respectively. Disease-free survival rates indicated median durations of 33 months (95%CI 32.949-34.545) at 3 years and 54 months (95% CI 53.063-56.357) at 5 years. Conclusion: This study enhances understanding of HER2+ breast cancer prognosis, emphasizing the critical roles of lymph node status, metastatic burden, and treatment strategies in determining patient outcomes.